The effect of catalyst precursors and conditions of preparing Pt and Pd-Pt catalysts on their activity in the oxidation of hexane - Kucharczyk Barbara; Szczygieł Bogdan; Chęcmanowski Jacek (Open Chemistry, 2017)
The effectiveness of under-air n-hexane oxidation over monolithic catalysts made of heat-resistant foil, containing Pt, Pd or Pt-Pd, was compared. Pt and Pd precursors, either containing chlorine or devoid of chlorine, were used to prepare the catalysts. The chlorine- containing Pt (H2PtCl6) and Pd (PdCl2) precursors were found to lower the activity of the catalysts in hexane oxidation. Studies of the effect of 0.15% Pt/Al2O3 catalyst (using H2PtCl6 as the precursor) calcination conditions on catalyst activity showed the catalyst calcined in static air at 500°C to be the most active. Airflow calcination of the catalyst does not change its catalytic properties. In comparison with the 0.5% Pd/Al2O3 catalyst obtained from Pd(NO3)2, the use of a bimetallic 0.5% Pd/0.1% Pt/Al2O3 catalyst, in which the precursors were Pd(NO3)2 and Pt(NO3)4, resulted in the lowering of 10% and 50% n-hexane temperature by 15°C and 10°C.